Penggunaan Memory Trick Game Dalam Meningkatkan Penguasaan Simple Past Tense Mahasiswa Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Bengkalis - Wan Julia Mayasari (STAIN Bengkalis, 2023)
The use of regular and irreguler verbs in Simple Past Tense always becomes a problem for students. If they can’t master well, the mistake always apperars. The aim of the study is to find out the significance of using Memory Trick Game in improving the students’ mastery of Simple Past Tense of English Study Program at STAIN Bengkalis. The samples are 20 English Study Program students. In collecting the data, a set of test was given to the samples namely; 1)pre-test and 2)post-test. Findings showed that mean of pre-test was 3.13 while mean of post-test was 4.63 where df = 42, ttable significance 5% = 2.02; in significance 1% = 2.72. In sum, Memory Trick Game was able to improve the students’ mastery of Simple Past Tense.